Secagem e armazenamento de sementes de Anadenanthera peregrina var. falcata (Benth.) Altschul e A. colubrina (Vell.) Brenan var. cebil (Griseb.) Altschul - Marques, Marco Antonio [UNESP] (2007)
This work was carried out with two brazilian tree species of the Anadenanthera genus (Mimosaceae): A. peregrina var. falcata and A. colubrina var. cebil , with the objectives of (a) to confirm the seed classification concerning both to the physiological behaviour during storage and to the longevity; (b) to conserve the seed physiological quality in medium-term storage; (c) to test drying methods for reduce safely to low values the seed moisture content; (d) to store dried seeds at sub-zero temperatures for a long-term storage. The seeds were dried over saturated salt solutions, over silica gel and by freeze-drying methods. Dried seeds were stored during different periods at room temperature, dry chamber, cold chamber, freezer, ultra-freezer and liquid nitrogen vapour phase. During storage, seed moisture content, germinability and vigour were evaluated. Seeds of both species showed orthodox behaviour and short longevity when stored at room temperature. The three drying methods were effective to reduce safely the seed moisture content. In medium-term storage, seeds maintained their physiological quality when (a) packaged into permeable container and stored at dry chamber; (b) packaged into impermeable container and stored at cold chamber; (c) freeze-dried, packaged into impermeable container and stored at room temperature. Dried seeds tolerated both low and ultra-low storage temperatures, showing possibility for long-term storage.